Social and Behavior Change Communication (SBCC) Approach in Tuberculosis Management by Terjang Foundation - Olih Solihin; Djuara Lubis; Pudji Muljono; Siti Amanah (UPT Publikasi Ilmiah UNISBA, 2023)
The treatment of TB faces many obstacles, both from the patient’s perspective and their environment. Therefore, the presence of TB survivors in the treatment process is expected to assist TB survivors during the recovery and post-recovery stages. Many approaches can be made to deal with TB, including the social and behavior change communication (SBCC) approach. This study aims to analyze the use of SBCC by TB survivors from the Terjang Foundation in treating TB in Bandung. This study adopts a qualitative research method with a case study approach. Data collection techniques include in-depth interviews, field observations, and literature reviews. The study results show that SBCC has been implemented as follows: 1) Advocacy is carried out through meetings to seek support from the government and other stakeholders; 2) Social mobilization is carried out by involving stakeholders, including the Health Office, community elements, and TB survivors. Social mobilization is conducted through TB Day activities, seminars, and patient visits; 3) Education is carried out by explaining TB treatment to survivors and accompanying TB patients during drug administration in hospitals.